Case report of a child with spontaneous pneumomediastinum and subcutaneous emphysema - Murtaza Ali Gowa; Syed Muhammad Aqeel Abidi; Bakhtawer Chandio; Hira Nawaz (Journal of International Medical Research, 2023)
Hamman’s syndrome is a rare clinical entity that presents with spontaneous pneumomediastinum and subcutaneous emphysema. It is most commonly diagnosed in young men and pregnant women, and is rare in children. We report the case of a female toddler who presented to an emergency department with fever, cough and shortness of breath. Imaging studies revealed subcutaneous emphysema and pneumomediastinum. The patient was diagnosed with Hamman’s syndrome after ruling out other possibilities. We discuss the underlying mechanisms of the disease, the diagnostic criteria and the treatment options. The purpose of this case report is to improve clinicians’ awareness of the existence of this rare clinical entity in paediatric patients.